INCREMENTAL CAPITAL OUTPUT RATIO: BAROMETER EFISIENSI PEREKONOMIAN NASIONAL - Muhamad Farid Mahmud (Jurnal Ilmiah Ekonomi Bisnis, 2011)
ICOR is used for determining ammount of investments which is required to achievetarget of national outputs. The value of the ratio is also representing efficiency ofeconomic of a country. The higher the value of the ratio the less efficient the country’seconomic is, indicating that the goverrment spending has not generated optimaloutputs. In other words, the country’s productivity is relatively low. Ordinary LeastSquare method were used to analyze time series data on real interets rates and othersbebas. variabels infulencing ICOR. Results of the study indicated that interest rate asan influencing variabel towards ICOR cannot be used as a solely policy instrument toincrease investement. In optimizing the nation’s output, a non conventional monetarypolicy, balanced infrastructure development, and poverty elimination programs seemto be required accordingly.